2015
DOI: 10.1007/s11227-014-1352-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing adaptive multi-device applications with the Heterogeneous Programming Library

Abstract: The usage of heterogeneous devices presents two main problems. One is their complex programming, a problem that grows when multiple devices are used. The second issue is that even if the codes for these devices can be portable on top of OpenCL, they lack performance portability, effectively requiring specialized implementations for each device to get good performance. In this paper we extend the Heterogeneous Programming Library (HPL), which improves the usability of heterogeneous systems on top of OpenCL, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…HPL has proven to be a good alternative to low level approaches like OpenCL or CUDA for programmability and performance as we can see in Viñas et al 8 and Viñas et al 12 Also, its evaluation in Viñas et al 9 showed that the usage of subarrays largely improved the programmability while having a negligible impact on performance when compared to native OpenCL. HPL has proven to be a good alternative to low level approaches like OpenCL or CUDA for programmability and performance as we can see in Viñas et al 8 and Viñas et al 12 Also, its evaluation in Viñas et al 9 showed that the usage of subarrays largely improved the programmability while having a negligible impact on performance when compared to native OpenCL.…”
Section: Programmabilitymentioning
confidence: 94%
See 4 more Smart Citations
“…HPL has proven to be a good alternative to low level approaches like OpenCL or CUDA for programmability and performance as we can see in Viñas et al 8 and Viñas et al 12 Also, its evaluation in Viñas et al 9 showed that the usage of subarrays largely improved the programmability while having a negligible impact on performance when compared to native OpenCL. HPL has proven to be a good alternative to low level approaches like OpenCL or CUDA for programmability and performance as we can see in Viñas et al 8 and Viñas et al 12 Also, its evaluation in Viñas et al 9 showed that the usage of subarrays largely improved the programmability while having a negligible impact on performance when compared to native OpenCL.…”
Section: Programmabilitymentioning
confidence: 94%
“…We will first focus on the programmability advantages of the mechanism to automatically synchronize ghost regions. HPL has proven to be a good alternative to low level approaches like OpenCL or CUDA for programmability and performance as we can see in Viñas et al 8 and Viñas et al 12 Also, its evaluation in Viñas et al 9 showed that the usage of subarrays largely improved the programmability while having a negligible impact on performance when compared to native OpenCL.…”
Section: Programmabilitymentioning
confidence: 94%
See 3 more Smart Citations